PREVALENCE OF PTOSIS IN CATARACT SURGERY PATIENTS AT A TERTIARY CARE CENTER IN ARUNACHAL PRADESH - NYAI ETE; TOJUM GONGO; PRAMOD KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of this study was to estimate the prevalence of ptosis in patients undergoing cataract surgery. Methods: This retrospective study, conducted in a tertiary care ophthalmology department, analyzed data from 520 adult cataract surgery patients over 6 months (July–December 2023). Of these, 88 patients had varying degrees of ptosis. Demographic details, medical history, and specific ophthalmic history were reviewed. Ptosis severity was assessed using margin-reflex distance 1 and levator function tests, categorizing ptosis as mild, moderate, or severe. The presence of any ocular abnormalities was noted. Keratometric readings were analyzed for astigmatism severity. SSPS 22.0 was used for statistical analysis and p<0.05 was taken as statistically significant. Results: In a study of 520 cataract surgery patients, 88 (16.92%) patients were found to have ptosis. Out of 88 cases with ptosis, there were 55 (62.50%) males and 33 (37.50%). The mean age of male and female patients was found to be comparable with no statistically significant difference. Bilateral ptosis (79 cases, 89.7%) was more common. Unilateral ptosis was observed in 9 (10.3%) cases. Mild ptosis was observed in 59 cases (67.05%), moderate in 21 cases (23.86%), and severe in 8 cases (9.09%). Ptosis was most commonly seen in age group of 61-70 years (34.09%) followed by 51-60 years (29.55%), above 70 years (20.45%) and 41-50 years (15.91%). The mean magnitude of astigmatism was 0.98 (±0.712) the mild ptosis, 1.39 (±0.953) for moderate ptosis, and 2.14 (±0.74) for severe ptosis, respectively. Conclusion: The presence of ptosis in patients undergoing cataract surgery can lead to suboptimal visual outcomes post-surgery. Addressing ptosis before cataract surgery ensures accurate lens selection and placement, enhancing patient satisfaction and visual acuity.